Iron nutritional status in female karatekas, handball and basketball players, and runners - Nuviala, R. J.; Castillo, M. C.; Lapieza, M. G.; Escanero, J. F. (Physiology & Behavior, 1996)
The iron nutritional status was studied in 84 sportswomen (19 karatekas, 20 handball players, 20 basketball players, and 25 middle and long distance runners) and in 82 nonathletic females of similar characteristics (control group). After a 7-day nutritional survey by means of the food weighing method, it was found that iron intake was significantly higher in the handball players (p < 0.05), basketball players (p < 0.01), and runners (p < 0.01) with regard to the control group; the basketball players were the only ones to cover the ecommended minimum intake (15 mg/day). The heme iron intake was significantly greater in the handball and basketball players (p < 0.01), who, together with the runners, reached the value of 1.5 mg/day, which is considered to be optimal. In relation to the control group, the karatekas and handball and basketball players had lower levels of serum ferritin, although their iron intake was greater, whereas the runners had higher values that were very similar to those of the control group, due to the iron supplementation they had received. Despite finding a marked prevalence of inadequate iron intake, both in the sportswomen and in the control group, the manifest cases of anemia are relatively scarce. The organic iron stores do not seem to depend exclusively on the iron intake but also on intimate mechanisms of intestinal absorption and diverse causes of iron loss.